Officer candidate tests for dummies - Burstein, Jane R. (For dummies, 2011)
Officer Candidate Tests For Dummies gives you the instruction and practice you need to pass the service-specific candidate tests and further your military career as an officer in the Army, Air Force, Navy, Marine Corps, or Coast Guard. This book gives you a comprehensive review of all subjects covered on the tests, an explanation of the test formats, and everything you need to understand and conquer the exams.